Patients’ perspective on informed consent in ear surgery - Adhikari, P; Guragain, RPS (Journal of Institute of Medicine Nepal, 2008)
Background: Informed consent is required before any surgical procedure. This study was done to assess patient's expectations before to signing consent forms for ear surgery. Methods: This study was done in Department of ENT and Head and Neck Surgery, T U Teaching Hospital from August to December 2006. All patients attending to OPD for appointment of surgery were randomly selected and were explained verbally about the possible complications of surgery, by the first author. There were 100 patients and they were interviewed with a standard questionnaire just one day before surgery. Answers were written by the first author on a standard questionnaire form. All those 100 patients who were informed previously about the possible complications were included in the study. Informed consent was obtained from all patients for the study. Data analysis was done statistically using frequency and percentage. Results: Ninety five percentages of patients were satisfied with the information given by doctors before ear surgery. There were very few patients (7.0%) who looked for further information. Only 27.0% patients could tell complication of ear surgery. Among them, 5.0% patients could list more than one complication. The common complications listed by our patients before ear surgery were bleeding (10.0%), infection (9.0%). Around 96.0% want to be informed all known complications even if the incidence was less than one percent. Conclusion: The information given by the doctors might not meet the expectation of the patients of twenty first century as they have a high expectation. However, the doctors should give a sufficient time to explain about the surgical procedure and they should not miss a common and important complication of surgery. Keywords: Informed consent, Patients expectation, Ear surgery. The full text of this paper is available at Journal of Institute of Medicine website